Comparison of breast ductal carcinoma in situ and ductal carcinoma in situ with microinvasion, and analysis of axillary lymph node metastasis. Issue 52 (24th December 2020) - Zhang, Geng; Li, Chunxiao; Tian, Guo; Cheng, Xiaozhi; Li, Yilun; Ma, Li
Abstract : Abstract: To compare the clinicopathologic features and long-term outcomes for women with ductal carcinoma in situ (DCIS) vs DCIS with microinvasion (DCISM), to assess the impact of microinvasion on tumor size and determine relationships between the number of microinvasive lesions and clinicopathological factors. A total of 493 patients with DCIS or DCISM from our database were analyzed to assess differences in clinicopathologic features and outcomes between the 2 cohorts. The median follow-up was 3.9 years, 229 patients had DCIS and 264 had DCISM, and the mean age was 46.8 years for the entire group. A total of 208 patients underwent axillary operation in the DCIS cohort vs 246 in the DCISM cohort, and the number of lymph node metastasis cases was 0 vs 13 for the 2 groups. For the lymph node-positive cases, the proportion of patients with no less than 3 microinvasive legions was 61.5% (8/13), while in the lymph node-negative group, the proportion of patients was 31.1% (78/251) ( P < .05). For the DCIS and DCISM groups, the relapse-free survival (RFS) values were 99.0% and 95.4% ( P = .034), while the overall survival (OS) values were 96.2% and 99.2% ( P = .032), respectively. Our data imply that for breast DCIS patients, axillary lymph node operation can be avoided, but for DCISM patients, surgical evaluation of the axilla is necessary. In addition, having no less than 3 microinvasive lesions in DCISM indicates poor prognosis. In the pathological staging of DCISM, tumor size and number of microinvasive lesions should be considered.